The Effect of Travel Personnel Knowledge on Compliance Levels With Covid -19 Health Protocols During the 14-Day Mandiri Isolation Period in Malaka District - Fahik, Paskalia Frida; Roga, Anderias Umbu; Ratu, Jacob M.; Nalle, Agus A.; Lada, Christina Olly (Advances in Social Sciences Research Journal, 2022)
The traveler from outside Malacca Regency carried out independent isolation for 14 days by implementing the COVID-19 health protocol, namely washing hands with soap under running water, wearing masks, maintaining distance, not crowding. This study aims to analyze the effect of the knowledge of travelers on the level of compliance with the COVID-19 health protocol, using a quantitative analytical research approach or method with a cross sectional study approach. The object of research is the knowledge of travelers in Wehali village, Central Malaka District, which was carried out in December 2020 by filling out a validated questionnaire. The population in the study was 58 respondents, the variables in this study were 2, namely the independent variable was the knowledge of the traveler and the dependent variable was adherence to the COVID-19 health protocol.